Sistem Cloud-Based Reporting Toko Retail menggunakan Framework Kivy dan Flask (Studi Kasus : PT. XYZ) - Nikson Theys Muay (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
XYZ is a company that provides daily needs. PT.XYZ has an idea to change the reporting system that has been used for years in the form of a desktop device into a newer application using a mobile device. PT.XYZ must replace gradually and cannot replace all devices as a whole, therefore this research was conducted to develop a new system, namely the Cloud-Based Reporting System for Retail Stores using the Kivy and Flask Frameworks, which in using the framework can create a system cross-platform, open source so that the system built can run on desktop and mobile devices which of course can be considered very efficient in reporting so that PT.XYZ can easily replace the old system without worrying about the transaction process. This research was conducted to develop a Cloud Based Reporting System using the waterfall process model. From the results of the tests carried out by the author, the percentage is 85.6% so it can be said that this test gets a very good response from potential users of the company PT.XYZ